Characterising keratometry in different dog breeds using an automatic handheld keratometer. (2nd May 2020) - Kawasaki, Minae; Furujo, Tomoya; Kuroda, Kohei; Azuma, Kazuo; Okamoto, Yoshiharu; Ito, Norihiko
Abstract : Background: Keratometry is clinically important and is routinely performed as part of human ophthalmic examination. In veterinary ophthalmology, little is known about keratometry in dogs, and its practical application has been limited. The present study aimed to describe keratometry in some dog breeds popular in Japan using a handheld keratometer. Methods: Client‐owned dogs of various signalment were enrolled prospectively in the keratometry examination. Interbreed variations in mean corneal curvatures (R1R2avg) and corneal astigmatism (Δ(R1−R2)) were evaluated statistically with respect to their bodyweight based on the data which fulfilled the predetermined inclusion criteria. P<0.05 was considered statistically significant. Results: On examination of 237 dogs from 16 different breeds, R1R2avg (mean±sd) ranged from 7.54±0.30 mm in Pomeranians to 9.28±0.19 mm in golden retrievers. Δ(R1−R2) (mean±sd) ranged from 0.22±0.11 mm in miniature schnauzers to 0.57±0.30 mm in French bulldogs. Conclusion: The present study successfully described keratometry in 16 dog breeds. The study revealed considerable interbreed variations in both R1R2avg and Δ(R1−R2), which did not necessarily correlate with bodyweight. These results are useful both clinically in fitting contact lenses in the management of corneal diseases and non‐clinically in optometric studies in dogs.